Field guide to leadership development - Kempster, Steve 1961-; Turner, Arthur F.; Edwards, Gareth (Edward Elgar Publishing, 2018)
This Field Guide offers a rich variety of academic approaches to facilitate leadership development in adults. It is an invaluable resource, giving insightful worked examples linked to theory and reflective commentary. The extensive experiences of world leading exponents of leadership development are distilled into practical application for immediate use
Keywords: Leadership